Challenges and proposals of the accounting profession for the development of sustainable economies Latinamerica - María González, José (2019)
The reports with non-financial information, especially environmental and social, through the use of various international standards have generated significant challenges in the Latin American accounting profession, both in terms of their knowledge and in the implementation in the various organizations, especially in the small and medium-sized companies, which are necessary factors for the sustainable economic development of the Region. The research project was developed through a structured survey to identify business activities that impact the Latin American environment, affecting sustainable economic development and also to highlight the social responsibility of organizations, by analyzing their Social Balances or Sustainability Reports. As a framework of theoretical reference, for this type of reports Accounting evolution and concepts are analyzed, especially the so-called Economic Accounting as well as new proposals such as the three-dimensional approach to Accounting. One of the most widely used standards in our Latin American region are the GRI Guidelines, but with little use by Small and Medium Enterprises. Therefore, it will be an interesting challenge to try to make a proposal that takes into account the characteristics of our Latin American SMEs in its preparation and in this way ensure that the public accountants have the corresponding academic training.